Anticancer Activity of Selective Cyclooxygenase-2 Inhibitor with Conventional NSAIDs - Mishra, Debasis; Ghosh, G.; Sudhir Kumar, P.; Panda, P.K. (Asian Journal of Chemistry, 2010)
Cyclooxygenase-2 (COX-2) is frequently detected in colon cancer and is believed to play a crucial role in colorectal carcinogenesis. The incidences of colorectal cancer were 0 % in group A, group B was taken as 100 %, 91 % in group C, 46 % in group D, 71 % in group E and 15 % in group F (p = 0.001, ANOVA). Compared with AOM controls, treatment with etoricoxib 10 mg/kg/day also showed lower ACF count and liver dysplasia. Although there is significantly higher COX-2 expression than their adjacent normal tissues, suggesting that the chemo preventive effect of etoricoxib may be mediated by a COX independent pathway. Treatment with etoricoxib (5 mg/kg) had no significant effect on number of ACF, treatment with etoricoxib (10 mg/kg) reduced colorectal cancer incidence and growth in rats.